The Effect of Smoking on The Recovery Time of Surgical Wounds - Sara Tanayah Uma; Dakari Cleo Denzel; Eifel Ayubi Azi; Ferezie Clevon Dalmar; Maisha Naaila Safiya; Lathaya Maha Ismitta (Indonesian Science Media, 2024)
Background: Cigarette consumption inhibits wound healing as nicotine and carbon monoxide interfere with blood flow, oxygenation, and immune function, increasing the risk of infection and prolonging wound recovery time. Purpose: To determine the effectiveness of modern dressing in wound care on diabetic wound healing. Methods: This study used a cross-sectional model to observe two groups: smokers (with a history of cigarette use) and a control group (non-smokers). Using purposive non-probability sampling, 9 smokers and 9 non-smokers meeting research criteria were selected, all undergoing elective surgery with sterile wounds. Data were analyzed with Spearman Correlation using SPSS version 12 Findings: The study involved 20 respondents, split evenly between smokers and non-smokers. Among the smokers, 48% were in the productive age group, and 68% consumed more than 10 cigarettes daily. All smokers use filtered cigarettes. Regarding wound healing, 79% of respondents experienced slow healing, 11% had optimal healing, 7% had standard healing, and 3% had rapid healing. Spearman Correlation test results indicated a significant relationship between smoking and wound healing time (p < 0.05), suggesting that cigarette consumption adversely affects the wound healing process. Conclusion: Smoking raises the risk of post-surgical infections, wound dehiscence, and delayed healing by causing inflammation, vasoconstriction, reduced oxygen delivery, and impaired cell recruitment. This highlights the importance of pre-surgery smoking cessation and further research to better quantify these effects and improve pre-operative treatments.